The influence of debond length on the buckling and wrinkling of sandwich beams under compressive load / Bambang K. Hadi (UPENA, 2007)
A two- and three-dimensional finite element analysis was carried out to analyze critical buckling loads of debonded sandwich beams. Both overall buckling and wrinkling were analyzed, using sandwich beams having 45 mm and 75 mm core thicknesses. The analysis shows that sandwich beams with 45 mm core thickness will exhibit overall buckling modes, while the ones with 75 mm core thickness will show wrinkling modes. The analysis also show that for sandwich beams having overall buckling modes, the existence of debond length of less than 10% of the sandwich beam length will only slightly reduce the buckling loads. However, the existence of debond on the sandwich beams having wrinkle modes will catastrophically reduce the buckling loads. Therefore, increasing the core thickness will not necessarily increase the capacity of sandwich beams in sustaining compressive forces. A good agreement is achieved when compared to experimental results.